Non-motor symptoms in genetically defined dystonia: Homogenous groups require systematic assessment. Issue 9 (September 2015) - Peall, K.J.; Kuiper, A.; de Koning, T.J.; Tijssen, M.A.J.
Abstract Introduction Dystonia is a movement disorder involving sustained or intermittent muscle contractions resulting in abnormal movements and postures. Identification of disease causing genes has allowed examination of genetically homogenous groups. Unlike the motor symptoms, non-motor characteristics are less clearly defined, despite their impact on a patient's quality of life. This review aims to examine the evidence for non-motor symptoms, addressing cohort size and methods of assessment in each study. Methods A systematic and standardised search strategy was used to identify the published literature relating to psychiatric symptoms, cognition, sleep disorders, sensory abnormalities and pain in each of the genetically determined dystonias. Studies were divided according to cohort size, method of assessment and whether comparison was made to an appropriate control group. Results Ninety-five articles were identified including reported clinical histories (n = 42), case reports and smaller case series (n = 12), larger case series (n = 23) and case-control cohorts (n = 18). Psychiatric symptoms were the most frequently investigated with anxiety, depression and Obsessive–Compulsive disorder being most common. Cognitive impairment involved either global deficits or isolated difficulties in specific domains. Disturbances to sleep were most common in the dopa-responsive dystonias. Sensory testing in DYT1 cases identified an intermediate subclinical phenotype. Conclusion Non-motor symptoms form an integral component of the dystonia phenotype. However, future studies should involve a complete assessment of all symptom subtypes in order to understand the frequency and gene-specificity of these symptoms. This will enable early symptom identification, appropriate clinical management, and provide additional outcome measures in future clinical trials.